Current state and the reasons for the transformation of aquatic ecosystems of the Ile river delta (Eurasian Journal of Ecology, 2018)
The study provides the results of modern state and the causes for thetransformation of aquatic ecosystems of Ile river delta in the period from1995 to 2015 years based on the data of water availability dynamics andhydrological regime of the Ile and study of multi-satellite images of theregion. Analysis of satellite images of the delta area in varying resolutionrevealed adjustment in hydrographic network of branches, channels andlakes of the Ile delta. Downward trend in area and drying ducts and lakesin the three main systems of the Ile delta (Topar, Ile and Zhideli) are shown.Key words: hydrographic network, the Ile river delta, streams, lakes,lake system, aquatic ecosystem, GIS technology, remote sensing methods